The Development Of Web-based Outcome Based Education Information System - Adip Safiudin; Sutrisno .; Meiyanto Eko Sulistyo; Subuh Pramono; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2020)
The development of Outcome Based Education (OBE) Information System is done as a solution to academic problems related to the achievement of graduate learning for students. In addition, the OBE system is a form of effort to improve academic quality in order to be able to monitor and measure the development of student learning outcomes in a college study program. The Outcome Based Education system includes all grades processing based on Course Learning Outcomes which is related to Graduates Learning Outcomes so that the outcomes of each student can be measured. This information system is developed by the Rapid Application Development method, and uses the Yii2 Framework with the concept of MVC (Model, View, Controller) where system programming is separated based on application components, such as: manipulating data, controllers, and user interfaces. The use of the RAD method and the Yii2 Framework in making applications can be done quickly and in a structured manner making it easier for future developments. The developed system has been successfully tested and applied in the Electrical Engineering Study Program, Civil Engineering Study Program and Mechanical Engineering Study Program, and planned to be implemented in all study programs of the Faculty of Engineering, Sebelas Maret University. This information system can be applied not only in the engineering faculty of Sebelas Maret University but also outside the university which requires an information system to measure the learning outcomes of graduates.